Agricultural resource use and management - Etingoff, Kimberly (Apple Academic Press, 2014)
Agriculture is one of the prime users of water, particularly in arid places with already-limited water resources, and its effects are diverse and far reaching. Providing a nuanced study of agricultural resource management, this informative book takes a four-pronged approach, covering research on: The impact of agriculture on water The impact of agriculture on soil quality and its ecological health Energy and greenhouse gases The impact of a growing population on agricultural resources.